An Assessment of the Ozone Loss During the 1999-2000 SOLVE Arctic Campaign - Burris, John F.; Bevilacqua, Richard; Grant, William B.; VonderGathen, Peter; Browell, Edward V.; Newman, Paul A.; McGee, Thomas J.; Richard, Eric; Einaudi, Franco; Schoeberl, Mark R.; Lait, Leslie R. (2001)
Ozone observations from ozonesondes, the lidars aboard the DC-8, in situ ozone measurements from the ER-2, and satellite ozone measurements from Polar Ozone and Aerosol Measurement III (POAM) were used to assess ozone loss during the Sage III Ozone Loss and Validation Experiment (SOLVE) 1999-2000 Arctic campaign. Two methods of analysis were used. In the first method a simple regression analysis is performed on the ozonesonde and POAM measurements within the vortex. In the second method, the ozone measurements from all available ozone data were injected into a free running diabatic trajectory model and carried forward in time from December 1 to March 15. Vortex ozone loss was then estimated by comparing the ozone values of those parcels initiated early in the campaign with those parcels injected later in the campaign. Despite the variety of observational techniques used during SOLVE, the measurements provide a fairly consistent picture. Over the whole vortex, the largest ozone loss occurs between 550 and 400 K potential temperatures (approximately 23-16 km) with over 1.5 ppmv lost by March 15, the end of the SOLVE mission period. An ozone loss rate of 0.04-0.05 ppmv/day was computed for March 15. Ozonesondes launched after March 15 suggest that an additional 0.5 ppmv or more ozone was lost between March 15 and April 1. The small disagreement between ozonesonde and POAM analysis of January ozone loss is found to be due to biases in vortex sampling. POAM makes most of its solar occultation measurements at the vortex edge during January 2000 which bias samples toward air parcels that have been exposed to sunlight and likely do experience ozone loss. Ozonesonde measurements and the trajectory technique use observations that are more distributed within the interior of the vortex. Thus the regression analysis of the POAM measurements tends to overestimate mid-winter vortex ozone loss. Finally, our loss calculations are broadly consistent with other loss computations using ER-2 tracer data and MLS satellite data, but we find no evidence for the 1992 high mid-January loss reported using the Match technique.